Analysis of biochars produced from the gasification of pinus patula pellets and chips as soil amendments - Gutiérrez , Jonatan; Rubio-Clemente, Ainhoa; Pérez, Juan F. (Maderas. Ciencia y Tecnología, 2022)
In this work, biochar (BC), a co-product of the fixed bed gasification process of Pinus patula wood pellets (PL) and chips (CH), was characterized as soil amendment. The physicochemical properties and the mineral content of the pellet’s biochar (PL-BC) and the chips biochar (CH-BC) were analyzed following the NTC5167 Colombian technical standard. The BET surface area values of the BCs were 367,33 m2/g and 233,56 m2/g for the PL-BC and the CH-BC, respectively, and the pore volume was 0,20 cm3/g for the PL-BC and 0,13 cm3/g for the CH-BC. These characteristics favor the increase of the BCs water-holding capacity (WHC). Properties such as the pH (8,8-9,0), the WHC (219 % - 186,4 %), the total organic carbon (33,8 % - 23,9 %), the metalloid presence (Ca, Mg, K, Mn, Al, Si, and Fe), and the ash (1,92 wt% - 2,74 wt%) and moisture contents (11,13 wt% - 11,63 wt%) for both BCs were found to be within the limits set by the NTC5167 standard. Furthermore, the presence of micro and macronutrients, such as Fe and phosphorus (P), and the alkaline pH, make possible the use of these BCs as amendments for acid soils.